2001
DOI: 10.1016/s0370-2693(01)00029-6
|View full text |Cite
|
Sign up to set email alerts
|

S-duality, noncritical open string and noncommutative gauge theory

Abstract: We examine several aspects of S-duality of four-dimensional noncommutative gauge theory. By making duality transformation explicit, we find that S-dual of noncommutative gauge theory is defined in terms of dual noncommutative deformation. In 'magnetic' noncommutative U(1) gauge theory, we show that, in addition to gauge bosons, open D-strings constitute important low-energy excitations: noncritical open D-strings. Upon S-duality, they are mapped to noncritical open F-strings. We propose that, in dual 'electric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 22 publications
(42 reference statements)
3
80
0
Order By: Relevance
“…In the case of compact Euclidean time the result of such a Tduality is to map a straight torus with a B-field into a tilted torus without a B-field. The spectrum is of course invariant under this transformation, so it is still given by the mass formula (23), except that w and n are interpreted in the IIA theory as momentum and winding, respectively. One should note that the second term, linear in B 01 , is no longer due to winding and the presence of a B-field, but to a mixing of momentum and energy resulting from the non-diagonal metric (30).…”
Section: B Is For Boostmentioning
confidence: 99%
“…In the case of compact Euclidean time the result of such a Tduality is to map a straight torus with a B-field into a tilted torus without a B-field. The spectrum is of course invariant under this transformation, so it is still given by the mass formula (23), except that w and n are interpreted in the IIA theory as momentum and winding, respectively. One should note that the second term, linear in B 01 , is no longer due to winding and the presence of a B-field, but to a mixing of momentum and energy resulting from the non-diagonal metric (30).…”
Section: B Is For Boostmentioning
confidence: 99%
“…By expanding on the complete set of energy eigenfunctions, after time translations, the loop acquires the expression (for Euclidean time) In the non-commutative case the Wilson loop can be defined by means of the Moyal product as [15,16] …”
Section: Time Exponentiation Of a Wilson Loop As A Test Of Unitaritymentioning
confidence: 99%
“…For fields transforming in 'adjoint' representations under the noncommutative gauge group, it has been shown that the only physical observables are the 'open Wilson lines' [6,3,4,5] along an open contour C:…”
Section: Introductionmentioning
confidence: 99%